Dominica : Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Dominica. (IMF Staff Country Reports; Country Report ;, 2009)
This staff report highlights Dominica's Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility. Although macroeconomic policy has been prudent and well-oriented, it is important to maintain the reform momentum. In this context, the key policy challenges facing the authorities are to stem the decline in economic activity resulting from the global downturn and to maintain a sustainable fiscal stance given the high public debt, and to improve competitiveness and reduce vulnerabilities to exogenous shocks.